RELACIÓN ENTRE LAS SUSTENTABILIDADES ECONÓMICA, ECOLÓGICA Y SOCIAL (Agroindustria, Sociedad y Ambiente, 2021)
Considering the transfer of knowledge as a social theory of thought; and sustainability from the perspective of human development, leads to work on the concept of sustainable development as the satisfaction of knowledge needs in the study of the transformations of society in the construction of the paradigm of development. The research sought to establish the relationship between Social and Natural Sciences for the transfer of knowledge between economic, ecological and social sustainability. Under a documentary design that allowed the selection of pre- analysis materials. The interpretation led to consider that sustainable development seeks the vision of the social sciences; taking from a pure science like biology the benefits to what surrounds us; occupying the emerging ecology of agronomy; as well as environmental impact studies. Sustainability arises from understanding the interaction between the physical, biological, social and economic, through values to promote the quality management of the environment in processes inherent to environmental management. Finally, in order to reach sustainable development, these three sustainability are necessary, which complement and contribute to the promotion of sustainability, as processes of knowledge.
Keywords: Science, Knowledge; Development, Gear and Sustainability.